PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Dina Safitri; Damayanti Damayanti (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This research aims to determine the effect of financial ratios on share prices in energy companies listed on the Indonesian Stock Exchange in 2017-2021 and obtained a sample of 15 companies determined by the purposive sampling method. The analysis technique used in this research uses panel data regression analysis with the E-Viwes 9 program as a data processing tool. The research results show that partially the liquidity ratio and activity ratio have an insignificant effect on stock prices and the solvency ratio has an insignificant positive effect on stock prices, while the profitability ratio has a significant effect on stock prices. And simultaneously the liquidity ratio, solvency ratio, profitability ratio, activity ratio have a significant effect on stock prices.